A Non-Negotiable Confession: Coming to Terms the Negotiable Instruments Law's Practical Irrelevance Amidst its Mandatory Instruction - Ty, Nicholas Felix L. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
Introduction; I. The Confession; II. Penance; III. Reconciliation; Conclusion.
Keywords: Negotiable instruments - Law; Negotiable instruments